From Neurocolonization to Cognitive Emancipation: The Critical Turn of Neurocapitalism - Zisi Yang; Ying Yang (Studies in Social Science & Humanities, 2025)
The deep development of digital capitalism has given rise to a new form of domination of neurocapitalism, which transforms human cognitive activities such as perception and memory into exploitable data resources through brain-computer interfaces and neural sensing technologies, forming an algorithmic hegemony to colonize cognitive systems. The traditional Frankfurt School critical theory encounters difficulties in explaining the operation of power in the age of neurotechnology, and the study reveals the multidimensional colonization mechanism of neurocapitalism with the help of the technological reconstruction of Habermas’s theory of interactional rationality and the dual critical framework of the phenomenology of technology-neuropolitical economy. Facing the systemic crisis of cognitive freedom, the cognitive alienation of neurocapitalism requires critical theory to shift from labor alienation to neuroalienation paradigm, to reconstruct the integrity of human subjectivity in the digital age by defending the autonomy of embodied cognition and the ethical limits of technological applications, and ultimately to guard the existential dignity of free will in the civilizational choices.